Franchising: The McDonaldization of Higher Education - Altbach, Philip (International Higher Education, 2012)
Universities and other institutions increasingly allow their degrees to be offered by providers abroad. This is called franchisingin many ways similar to what McDonalds does, but in the field of higher education. There are frequently problems of low quality, inadequate supervision, and others. Key Words: McDonalization, offshore degrees, problems of quality assurance.